Perang Obor Jepara : Sejarah Lokal Ritual dan Perayaan di Jepara Tahun Sejak 1990-an - Safitri, Ramadina (Historia Pedagogia, 2024)
This research aims to uncover the local history of Jepara Regency that occurred around the 1990s. The ritual in question is Perang Obor (Torch War), a unique tradition passed down through generations by the local community. Perang Obor is a traditional ceremony performed as an expression of gratitude to God and a request for protection from various disasters. This tradition is also considered a symbol of courage and unity among the villagers. In this study, archival and document study methods were used to gather data, by examining various written sources such as historical records, government documents, and newspaper articles documenting the ritual in the past. The research findings indicate that Perang Obor serves not only as a religious rite but also as a means of maintaining social solidarity and the cultural identity of the Jepara community. This tradition has continued to survive to this day, albeit with some adjustments to fit the times. This study is expected to contribute to the preservation of local culture and raise public awareness of the importance of safeguarding ancestral traditions.